2005
DOI: 10.1590/s1516-89132005000800010
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella enteritidis on raw poultry using microwave heating

Abstract: The effect of microwave heating on Salmonella Enteritidis inoculated on fresh chicken was investigated using a microwave oven (800 w) to determine the destruction of Salmonella Enteritidis isolated from chicken carcasses, in relation to the time of heating at two power settings: high (power level 10) and medium (power level 6); The relationship between heating time and temperature was also been studied. The destruction was 6.4 log cycles at time 95 sec for the high power level, and 5 log cycles at time 140 sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…In agreement with Aziz et al (2002), Canumir et al (2002) and Pucciarelli and Benassi (2005), the effectiveness of microwaving as a means of bacterial inactivation was demonstrated even in the heavily contaminated products after 8 days storage. However, this heat treatment does not inactivate pre-formed toxins or preclude the survival of pathogens or spoilage microorganisms in the viable-but-non-culturable state in these products.…”
Section: Discussionsupporting
confidence: 75%
“…In agreement with Aziz et al (2002), Canumir et al (2002) and Pucciarelli and Benassi (2005), the effectiveness of microwaving as a means of bacterial inactivation was demonstrated even in the heavily contaminated products after 8 days storage. However, this heat treatment does not inactivate pre-formed toxins or preclude the survival of pathogens or spoilage microorganisms in the viable-but-non-culturable state in these products.…”
Section: Discussionsupporting
confidence: 75%
“…The predominant serotypes vary in different countries, In Argentina, S. Typhimurium was predominant in outbreaks of gastroenteritis until 1987 (Pucciarelli and Benassi 2005). Although S. Enteritidis is the most frequently isolated serovar from the eggshells and egg contents in many countries (Musgrove et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in agreement with others; although, these results have been deduced from a pilot study. The predominant serotypes vary in different countries, In Argentina, S. Typhimurium was predominant in outbreaks of gastroenteritis until 1987 (Pucciarelli and Benassi 2005). Although S. Enteritidis is the most frequently isolated serovar from the eggshells and egg contents in many countries (Musgrove et al 2005), it seems that the most frequent isolate from eggs in Iran is S. Typhimurium (Jafari et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Jamshidi and others (2010) reported that E. coli O157:H7 can be largely reduced (>4 log CFU/cm 2 ) on beef slices (200 g), with a 30‐s exposure to 850 W MW heating. Pucciarelli and Benassi (2005) studied the inactivation of Salmonella enteritidis on raw poultry and presented a 6.4‐ and 5.0‐log reductions with 800 W (95 s) and 500 W (140 s) MW heating, respectively.…”
Section: Introductionmentioning
confidence: 99%